Evaluation of Combined Sewer Network Design Using GIs and Multi Criteria Decision Making (MCDM) - Najeeb, Zeena Adil (Al-Nahrain Journal for Engineering Sciences, 2017)
In this Research Geometric network modeled for combined sewer network pipe design were establish for AL-Nahrain University site by Arc map and GIS tools which is built within a feature dataset in the geodatabase. The geometric networks consist of lines and points which refer to the pips and junctions respectively. Data were collected for manholes location, flow direction, slop and elevations. Many influencing features were used in multi criteria decision making (MCDM) vie Super decision 2.0.8 software which be selected to fix the problem and find the alternative for two sewer networks. The first sewer network (A) considered the existing one and the second was the alternative one (B) , Bentley sewer Cad V8 have the ability to work with ArcGIS program as a part of it by export data as shape file from GIS then by scenario report form program that exam the part of network and find the alternative . The purpose of this research was to use this data GIS model, and developed it in future event by predicting some function like rainfall amount or adding population increasing density represent by both student and employers. As a result using (ANP) analysis this method allow to make consideration alternative we found the network(A) need to add some routs depending in the amount of person daily consumption with the amount of rain fall Intensity for the next years., judgment based on expert advice is obtained through pair-wise comparisons. Afterwards, the corresponding matrix is established, and sanity of the comparisons is checked by super decision software. Finally Existing network (A) shows highest benefit score and efficiency in this time for steady case depends on two criteria coast and optimum flow for person consumption.